HUBUNGAN AKSES DAN MOTIVASI IBU DENGAN PEMBERIAN IMUNISASI DASAR PADA BAYI 0-11 BULAN DI DESA LUMBAN TORUAN WILAYAH KERJA PUSKESMAS KENTARA KECAMATAN LAEPARIRA KABUPATEN DAIRI TAHUN 2019 - lidya marbun; Rismahara lubis; Arihta Sembiring (Poltekkes Kemenkes Medan, 2020)
Basic immunization is given to prevent various diseases, including hepatitis B, tuberculosis, diphtheria, pertussis, tetanus, polio and measles. Based on the data found, basic immunization coverage is still below the target. The condition was caused by the family not allowing and immunization service places far from their homes. This study aims to determine the relationship between access and motivation of mothers with basic immunization for infants aged 0-11 months in Lumban Toruan Village, Kentara Health Center, Dairi District, 2019. This type of research is analytic with cross sectional design. The population in this study were all mothers with babies aged 0-11 months who visited the Posyandu in Lumban Toruan village as many as 34 people. The sample used is total population. The data used are primary and secondary data, instruments used in questionnaires, data analysis using statistical tests, namely Chi-Square test with ? <0.05. The results showed that there was a relationship between access and basic immunization for infants aged 0-11 months in Lumban Toruan Village, Kentara Health Center Work Area, Dairi Regency in 2019, with a value of ? = 0.001 (<0.05). There is a relationship between maternal motivation and basic immunization for infants aged 0-11 months in Lumban Toruan Village, Kentara Health Center Work Area, Dairi Regency in 2019, with a value of ? = 0.001 (<0.05). It is hoped that health workers in Lumban Toruan Village will improve information or counseling about the importance of basic immunization and make home visits for mothers with 011 months infants who have difficult access to improve the health status of infants.